Development and characterization of DNA aptamer and microfluidic paper based platform for detection of heart type fatty acid binding protein - Kakoti, Ankana (My University, 2016)
The current investigation is centered on the development of specific aptamers against human heart type fatty acid binding protein (FABP3), a novel early marker for detection of acute myocardial infarction (AMI). It also encompasses the detection of FABP3 using the developed aptamers on a specially designed paper based microfluidic device (µPAD). For generating specific aptamers for FABP3, recombinant FABP3 was selected as the target while recombinant FABP1, FABP4 and FABP7 were chosen as controls. The coding sequences of all the four proteins were separately sub cloned into the pGEX-4T2 expression vector and transformed into BL21 (DE3) cells. Recombinant FABP3, FABP1 and FABP4 expression was induced at an IPTG concentration of 100 µM for 12 hrs at 37 oC, while expression of FABP7 was accomplished at an IPTG concentration of 50 µM for 12 hrs at 30 oC. The recombinant proteins were purified using glutathione agarose affinity chromatography and confirmed by SDS-PAGE and Western blots. All the recombinant proteins retained their correct secondary structures suggested by their CD spectra which were dominated by β-sheets. Systematic Evolution of Ligands by Exponential Enrichment (SELEX) was employed to generate aptamers against FABP3. A total of 20 SELEX cycles were performed, out of which 8 were counter SELEX cycles incorporating the control proteins. The enriched pool was cloned into TA vectors and the positive clones were selected on the basis of blue-white screening and restriction enzyme digestion.
Goswami, Pranab
Keywords: BIOSCIENCES AND BIOENGINEERING